Quantitative determination of lurbinectedin, its unbound fraction and its metabolites in human plasma utilizing ultra-performance LC–MS/MS - Nicholas King; Soledad Garcia-Martinez; Eider Alcaraz; Alba Grisalena; Rubin Lubomirov; Raquel Altares; Carlos Fernandez-Teruel; Andrés M. Francesch; Pablo M. Avilés; Salvador Fudio (PLoS ONE, 2023)
Aims Ultra-performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) methods to quantify total lurbinectedin, its plasma protein binding to derive the unbound fraction and its main metabolites 1′,3′-dihydroxy-lurbinectedin (M4) and N-desmethyl-lurbinectedin (M6) in human plasma, were developed and validated. Materials & methods For lurbinectedin, sample extraction was performed using supported liquid extraction. For metabolites, liquid-liquid extraction with stable isotope–labeled analogue internal standards was used. Plasma protein binding was evaluated using rapid equilibrium dialysis. In vitro investigations at different plasma protein concentrations were carried out to estimate dissociation rate constants to albumin and alpha-1-acid glycoprotein (AAG). Results Calibration curves displayed good linearity over 0.1 to 50 ng/mL for lurbinectedin and 0.5 to 20 ng/mL for the metabolites. Methods were validated in accordance with established guidance. The inter-day precision and accuracy ranged from 5.1% to 10.7%, and from -5% to 6% (lurbinectedin in plasma); from 3.1% to 6.6%, and from 4% to 6% (lurbinectedin in plasma:PBS); from 4.5% to 12.9%, and from 4% to 9% (M4); and from 7.5% to 10.5%, and from 6% to 12% (M6). All methods displayed good linearity (r2 >0.99). Recovery was evaluated for lurbinectedin in plasma:PBS (66.4% to 86.6%), M4 (7.82% to 13.4%) and M6 (22.2% to 34.3%). The method for lurbinectedin in plasma has been applied in most clinical studies, while the plasma:PBS and metabolites methods were used to evaluate the impact of special conditions on lurbinectedin PK. Lurbinectedin plasma protein binding was 99.6% and highly affected by AAG concentration. Conclusions These UPLC–MS/MS methods enable the rapid and sensitive quantification of lurbinectedin and its main metabolites in clinical samples.